2014
DOI: 10.1039/c4md00185k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, DNA binding, docking and photocleavage studies of quinolinyl chalcones

Abstract: A series of simple quinoline-chalcone conjugates have been synthesized by Claisen-Schmidt condensation reactions of substituted acetophenones with 2-chloro-3-formyl-quinoline and evaluated for their nucleolytic activity. The structures of the synthesized quinoline-chalcone conjugates were confirmed by IR, 1 H NMR, 13 C NMR and mass spectral analyses. Most of the prepared compounds showed significant DNA binding and photocleavage activities. The incorporation of an electron-donating group into ring A caused a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Compounds with formyl group have a wide range of applications in the synthesis of functional organic molecules such as fluorescent dyes [5][6][7][8], bioactive molecules [9][10][11] and photoelectric materials [12]. Formyl groups can be oxidized to carboxyl groups and reduced to alcohol for further reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds with formyl group have a wide range of applications in the synthesis of functional organic molecules such as fluorescent dyes [5][6][7][8], bioactive molecules [9][10][11] and photoelectric materials [12]. Formyl groups can be oxidized to carboxyl groups and reduced to alcohol for further reaction.…”
Section: Discussionmentioning
confidence: 99%
“…-O(3), Si(1)-C(10), Si(1)-C(11), Si(1)-C(12), and O(3)-C(2) bond lengths are found to be 1.6802(13) Å, 1.858(2) Å, 1.858(2) Å, 1.8740(19) Å, and 1.369(2) Å, respectively, which are within the range expected for similar single bonds. The bond lengths of O(1)-C(7) and O(2)-C(8) are found to be 1.202(3) and 1.201(2) Å, respectively, in accordance with a typical carbonyl double bond.…”
mentioning
confidence: 99%
“…A series of simple quinoline-chalcone hybrids were synthesized by Bindu et al 218 and screened for their nucleolytic activity. Most of the synthesized compounds displayed signicant DNA binding and photocleavage activities.…”
Section: Quinoline-chalcone Hybrids As Kinase Inhibitorsmentioning
confidence: 99%
“…The results revealed that compound 47 experienced high concentration-dependent DNA cleavage activity. This activity is believed to be enhanced by iminyl and carboxy radicals of 2-chloro-3-(5-aryl-4,5-dihydroisoxazol-3-yl)quinolines, 219 Fig. 7.…”
Section: Quinoline-chalcone Hybrids As Kinase Inhibitorsmentioning
confidence: 99%
“…Small-molecule interactions with DNA continue to be intensely and widely studied for their usefulness as probes of cellular replication and transcriptional regulation and for their potential as pharmaceuticals [72][73][74][75]. In particular, designing of the compound based on their ability to cleave DNA is of great importance not only from the primary biological point of view but also in terms of photodynamic therapeutic approach to develop potent drugs [72][73][74][75]. 1,4-Dihydropyridine derivatives have attracted the attention of the chemists because of their diverse biological applications [76].…”
Section: Introductionmentioning
confidence: 99%